1985
DOI: 10.1121/1.392223
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft noise annoyance at three joint air carrier and general aviation airports

Abstract: The results of social surveys conducted near three airports that support both general aviation and scheduled air carrier operations are presented and discussed. Inferences supported by these data include: The nature of noise exposure and community reaction at smaller airports may differ from that at larger airports; survey techniques are capable of identifying changes in annoyance associated with numerically small changes in noise exposure; changes in the prevalence of annoyance are causally produced by change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…It has been hypothesized ͑Fidell et al., 1985;Van Kempen and Van Kamp, 2005͒ that public awareness or the expectancy of an upcoming change alone may be enough to evoke an advanced over-reaction so that higher-thanpredicted annoyance would be reported by respondents even before an exposure change actually takes place. Although the upcoming changes in the flight regime were announced in the media for more than a year in advance, we found no evidence that the eastern residents prematurely "reacted" to the future noise situation.…”
Section: Influence Of An Exposure Change On Annoyancementioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized ͑Fidell et al., 1985;Van Kempen and Van Kamp, 2005͒ that public awareness or the expectancy of an upcoming change alone may be enough to evoke an advanced over-reaction so that higher-thanpredicted annoyance would be reported by respondents even before an exposure change actually takes place. Although the upcoming changes in the flight regime were announced in the media for more than a year in advance, we found no evidence that the eastern residents prematurely "reacted" to the future noise situation.…”
Section: Influence Of An Exposure Change On Annoyancementioning
confidence: 99%
“…As such parameters change, they usually elicit a step change in exposure. There is evidence that a step change of noise exposure generally goes along with a so called "over-reaction" of the residents: With an increase of the exposure level, people are more annoyed than would be predicted by steady-state exposure-effect curves, whereas with a decrease of the level, they are less annoyed than would be predicted by the same curves ͑Fidell et al., 1985;Fidell et al, 2002;Griffiths and Raw, 1989͒. Although some models and tentative explanations have previously been published ͑Job, 1988b; Job and Hatfield, 2003͒, the mechanism of how residents judge their level of annoyance in response to the exposure change is not understood in detail.…”
Section: A Influence Of a Step Change In Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the distribution of #yover noise levels in some areas near small airports can be highly bimodal. It is also possible that for the same aircraft¸" , values, residents of neighbourhoods near the small airport might simply hear more over#ights than residents of neighbourhoods near the large airport [32]. In this study, there were weaker associations between noise map information and the self-report of noise exposure for road tra$c noise.…”
Section: Discussionmentioning
confidence: 80%
“…Langdon and Griffiths ͑1982͒ noted such a possibility for residents' perception of the public policy of authorities and that this possibility was first suggested by Scholes ͑1977͒. Fidell et al ͑1985͒ suggested that heightened community awareness might plausibly be sufficient to account for a greater prevalence of self-reported annoyance.…”
Section: Attitudes Toward the Source/authorities Changementioning
confidence: 98%